Measurements of solution fluorescence – a new concept - Gębala, Stefan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The presented studies are based on the predictions of the behavior of certain types of fluorescence pigments in water solutions. Their asymmetric structure causes spontaneous surface concentration of the investigated sample. As a result, a densely packed, organized surface layer is created. This layer facilitates much better conditions for fluorescence than the rest of a sample. A set-up for solution surface fluorescence measurements has been assembled. This paper presents the results of the studies which confirm the occurrence of this phenomenon. The studies involved testing several biological samples. The described concept of fluorescence measurement has significant practical aspect.
Optica Applicata, Vol. 39, 2009, nr 2, s. 391-399
Keywords: optyka; fluorescence; amphophility; surface self concentration; liquid crystal